2009
DOI: 10.1111/j.1479-828x.2009.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based carrier screening for cystic fibrosis in Victoria: The first three years experience

Abstract: Carrier screening for CF by obstetricians and general practitioners by cheek swab sample can be successfully undertaken prior to pregnancy or in the early stages of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 8 publications
1
65
0
Order By: Relevance
“…42,50,53,64,73 Individual carrier status did not affect reproductive intentions or behaviors, with carriers not altering their reproductive plans after receiving a positive test result. [65][66][67]71,73,[76][77][78] Screening of partners of carriers to determine risk of having a child with CF had an uptake of 61-100%, 20,36,52,74,[78][79][80][81][82][83] with reasons for partners not being tested being as follows: anxiety about result; would be tested when planning to start a family; would not alter reproductive plans; and had no further reproductive plans. 74,78 When participants were asked to consider their reproductive intentions if they were found to be a carrier couple, the majority stated that they would not have (more) children, 10,71 would utilize prenatal diagnosis in future pregnancies, 10,52,71 were unsure, or would not terminate an affected fetus.…”
Section: Outcomes and Follow-up Of Screening For Cf Carrier Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…42,50,53,64,73 Individual carrier status did not affect reproductive intentions or behaviors, with carriers not altering their reproductive plans after receiving a positive test result. [65][66][67]71,73,[76][77][78] Screening of partners of carriers to determine risk of having a child with CF had an uptake of 61-100%, 20,36,52,74,[78][79][80][81][82][83] with reasons for partners not being tested being as follows: anxiety about result; would be tested when planning to start a family; would not alter reproductive plans; and had no further reproductive plans. 74,78 When participants were asked to consider their reproductive intentions if they were found to be a carrier couple, the majority stated that they would not have (more) children, 10,71 would utilize prenatal diagnosis in future pregnancies, 10,52,71 were unsure, or would not terminate an affected fetus.…”
Section: Outcomes and Follow-up Of Screening For Cf Carrier Statusmentioning
confidence: 99%
“…74,78 When participants were asked to consider their reproductive intentions if they were found to be a carrier couple, the majority stated that they would not have (more) children, 10,71 would utilize prenatal diagnosis in future pregnancies, 10,52,71 were unsure, or would not terminate an affected fetus. 23,52,57 In actuality, 80-100% of the carrier couples identified utilized prenatal diagnosis, 38,39,41,51,60,66,75,[78][79][80]82,84,85 and the majority terminated an affected fetus. 38,51,60,66,75,79,80,82,84 Only one study reported the continuation of an affected pregnancy, with the carrier couple having twins who were both identified as being affected.…”
Section: Outcomes and Follow-up Of Screening For Cf Carrier Statusmentioning
confidence: 99%
“…In Victoria, Australia, CF carrier screening is offered as a feefor-service (AUD$200 per person) to women planning pregnancies and those in early pregnancy. Initially (2006) offered through obstetricians in private practice, i.e., requiring referrals in Australia, it was later expanded to GPs in 2007 (Massie et al 2009). Pre-test information is provided by the physician, together with written information about CF and screening.…”
Section: Preconception Carrier Screening For Cf In Primary Carementioning
confidence: 99%
“…It is currently a fee-forservice programme with each test costing AUD$220. During the first 3 years of the programme (2006)(2007)(2008), 3,200 individuals were screened, all partners of carriers were screened and carrier couples used the information received to make reproductive decisions (Massie et al 2009). In 2008, we conducted a study exploring the attitudes and outcomes of individuals who accepted CF carrier screening, excluding carrier couples, through this programme (Ioannou et al 2010).…”
Section: Introductionmentioning
confidence: 99%